Potential of freely available remote sensing visible images to support growers in delineating within field zones. (1st June 2017) - Crestey, T.; Pichon, L.; Tisseyre, B.
Abstract : Remote sensing images offer a unique monitoring capacity for agriculture fields. Despite significant drawbacks, free historical remote sensing images are likely to provide valuable information to delineate temporally stable zones, especially for a perennial crop like vines. In order to test the potential of these free images for delineating within field soil zones, an experiment was performed on three vine fields located in southern France. On each vine field, the grower was asked to delineate within field zones that present differences in soil characteristics. The first expert zoning (ZP zoning) was only based on the grower's knowledge. Two weeks after, 12 visible free remote sensing were provided to the grower to refine the first zoning (ZAI zoning). In order to assess the relevancy of both zonings, a soil apparent electrical conductivity (ECa) survey was performed on each field. The Rv zoning index was then computed on ECa data to assess the potential improvement between ZP and ZAI zonings. Results show that for two fields, remote sensing images improved the zoning while for one field both ZP and ZAI expert zonings were similar. This result highlights a potential interest in historical remote sensing images to improve the knowledge that growers have of their fields. It should be noted, however, that this improvement is still limited in the case of viticulture where the small size of the fields with a large number of manual operations is likely to lead to a good knowledge of within field variability.